What educational management are we talking about? A case study on educational management at local government level in two townhalls in Piura, Peru (Revista Peruana de Investigación Educativa, 2012)
This paper presents the results of a study on the rationales and management of educational services in two local districts in the city of Piura, Peru. The study is based on two hypotheses: (1) heterogeneity affects the ability of local governments to be in charge of educational competencies, and (2) managing involving participatory practices creates better performance conditions. The study focused on observing the priority of education in the rational of municipal management, within a framework of changes that demands the decentralization and administrative reform of the state government.In order to account for the changes in regulations and administration in the decentralization process, an approach of bureaucratic configurations is adopted to address the institutional heterogeneity of state government. The organizational structure of both municipalities considered is analyzed within local context, considering structural hierarchies and internal coordination levels, their composition and organization, the dynamics of work activities by municipal clerks and employees, and the available budget and spending.The analysis of local government management provides the basis for assessing educational management in both municipalities. The managerial strategies of educational services are explored, considering the municipal prospective on management. In the cases studied it is found that, with different implications, political legitimation is tangled up with technical rationalization, which results in a detriment to efforts for improving education. This does not imply that there might not be proper conditions for building local models of educational management, but that there are rather complex variables and interests that constraint municipal action and participation in management. This work is aimed at contributing to the debate on the role of local governments in managing education.
Keywords: Educational management; educational decentralization; organization and management; bureaucracy; institutionalization